Aerodynamic evaluation of the empty nose syndrome by means of computational fluid dynamics. Issue 14 (26th October 2017) - Balakin, Boris V.; Farbu, Erlend; Kosinski, Pawel
Abstract: The potential outcome of a surgical enlargement of internal nasal channels may be a complication of nasal breathing termed the Empty Nose Syndrome (ENS). ENS pathophysiology is not entirely understood because the expansion of air pathways would in theory ease inhalation. The present contribution is aimed at defining the biophysical markers responsible for ENS. Our study, conducted in silico, compares nasal aerodynamics in pre- and post-operative geometries acquired by means of computer tomography from the same individual. In this article, we elucidate and analyse the deviation of airflow patterns and nasal microclimate from the healthy benchmarks. The analysis reveals 53% reduction in flow resistance, radical re-distribution of nasal airflow, as well as dryer and colder nasal microclimate for the post-operative case.